2022
DOI: 10.1001/jamanetworkopen.2022.26816
|View full text |Cite
|
Sign up to set email alerts
|

Risk of SARS-CoV-2 Acquisition in Health Care Workers According to Cumulative Patient Exposure and Preferred Mask Type

Abstract: This cohort study compares the risk of infection with SARS-CoV-2 among health care workers by mask preference and level of patient exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…This is in line with several previous studies 10 , 13 . Many authors reported a strong positive association between SARS-CoV-2 infection and being in contact with a COVID-19 case at home, including in Switzerland (aOR, 7.79; 95% CI, 5.98–10.15) 9 , in France (aOR 2.00; 95% CI 2.23–3.28) and in Belgium (aOR 3.15; 95% CI 2.33–4.25) 7 , 14 . In contrast to some studies conducted among hospital HCWs 7 , but consistent with others 10 , 11 , we did not find associations between the SARS-CoV-2 infection and workplace factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with several previous studies 10 , 13 . Many authors reported a strong positive association between SARS-CoV-2 infection and being in contact with a COVID-19 case at home, including in Switzerland (aOR, 7.79; 95% CI, 5.98–10.15) 9 , in France (aOR 2.00; 95% CI 2.23–3.28) and in Belgium (aOR 3.15; 95% CI 2.33–4.25) 7 , 14 . In contrast to some studies conducted among hospital HCWs 7 , but consistent with others 10 , 11 , we did not find associations between the SARS-CoV-2 infection and workplace factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The same two hypotheses (true association in bivariate analyses but lack of power to show it in multivariate analyses, or biased association in bivariate analyses by confounding factor) may explain the significant association in bivariate analyses between the use of mask and the infection. It was reported in some studies with both occupational and non-occupational factors associated with SARS-CoV-2 infection, that the strongest predictor of contracting COVID-19 was exposure to an infected person outside work 9 , 14 . Our findings are in lines with the fact that for PHCWs, the risk of SARS-CoV-2 infection from community exposure may be more significant than the risk of occupational exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective analysis showed that use of KN95/N95 respirators by both community members [47] and in healthcare settings [48] resulted in lower COVID infection rates as compared to cloth and surgical masks. Across a variety of manufacturers the average filtration efficiency of N95 at\ 0.3 μm particle size was found to be much higher at 98% and more consistent than 81% for KN95 (Table 2 of [49]).…”
Section: Introductionmentioning
confidence: 99%
“…Ironically, readers of the article may use the putative connection between respirators and complications of airway management as an argument not to wear respirators during patient care, which in our opinion, puts patients and clinicians at greater risk of infection with dangerous pandemic respiratory pathogens. Notably, a recently published study has provided evidence that respirators protect healthcare workers from infection [ 5 ].…”
mentioning
confidence: 99%